The Religious Aspect of Art in Contemporary Civilizational Imagination - Rubavičius, Vytautas (Religija ir kultūra, 2016)
[full article and abstract in Lithuanian; abstract in English] This article discusses the ongoing strengthening of civilizational imagination and civilizational self-awareness, which are currently being observed in various regions of the world, both on the political and geopolitical levels. Based on insights from Samuel P. Huntington, his ideas about the significance of religion for civilization and the interactions of civilizations are raised. This article outlines the importance of religious and artistic heritage for civilizational imagination and states that the religious heritage of imperial civilizations is always embodied in artistic forms and artistic practices, which, in turn, always have a religious feature. The main focus is on the peculiarities of the revival of the Turkish civilizational imagination, trying to explain the spread of neo-Ottoman ideology and ideas in the field of culture, while this ideology becomes the political and geopolitical instrument that forms a new Turkish identity. The image of the “collision” between Islam and Western civilizations is revealed in Orhan Pamuk’s novel My Name Is Red. The article posits this work as an example showing how artistically contemplated history becomes an important tool for strengthening the current civilizational imagination, which also has a huge religious dimension.